Financial Performance of Manufacturing Companies - Chaidir, Randy; Herman (International Journal of Business and Applied Economics, 2024)
The purpose of this research is to identify the effect of debt policy and profitability on company value. This study uses secondary data acquired from manufacturing companies listed on the Indonesia Stock Exchange in the period of 2018-2022. Using purposive sampling, 195 companies meeting the predetermined criteria were selected as the sample. The results of the Moderated Regression Analysis have led to the following findings. Debt policy and profitability positively affect firm value.